Towards an integrated framework of intrinsic motivators, extrinsic motivators and knowledge sharing. Issue 6 (9th October 2017) - Law, Kuok Kei; Chan, Andrew; Ozer, Muammer
Abstract : Purpose: This paper aims to develop an integrated framework to demonstrate the individual and combined effects of intrinsic and extrinsic motivators on two forms of knowledge sharing behaviors – in-depth knowledge sharing and routinized knowledge sharing. Design/methodology/approach: A range of work on the use of intrinsic and extrinsic motivators and the differential degrees of costs and risks involved in the two forms of knowledge sharing is being reviewed with the aim to locate gaps and problems arising from propositions of different scholars. An integrated framework is then proposed to connect different schools of thoughts into a single, unifying framework. Findings: Knowledge sharing behaviors among employees are subject to both attractive and distractive forces. Intrinsic and extrinsic motivators might interact positively or negatively depending on the type of extrinsic motivator and the form of knowledge sharing. While enhancing the intrinsic enjoyment of employees along with outcome-based extrinsic motivators can promote in-depth knowledge sharing, the use of behavior-based extrinsic motivators is more appropriate for fostering routinized knowledge sharing. Research limitations/implications: This paper mainly focuses on the sharing of knowledge without examining the receiver side in knowledge sharing. Also, the use of punitive means by superiors in encouraging knowledge sharing is not discussed in the framework. Future research can also add into the authors' integrated framework the effects of personal traits in knowledge sharing. Originality/value: This paper narrows the gap between existing theories on the use of extrinsic and intrinsic motivators and offers an integrated theoretical framework for those interested in examining the inter-relationship among intrinsic motivators, extrinsic motivators and knowledge sharing behaviors.